A critical evaluation on chemical exergy and its correlation with high heating value for single and multi-component typical plastic wastes. (1st August 2018) - Huang, Y.W.; Chen, M.Q.; Li, Q.H.; Xing, W.
Abstract: Chemical exergy of plastic waste is very critical for the optimization design of its thermochemical conversion system. The chemical exergy of six kinds of typical plastic wastes was calculated. The linear relationship between chemical exergy and high heating value for the samples was identified. The universal set of simulated multi-component plastic wastes was divided into five subsets based on the number of the components. The sample set was generated from five subsets by using the systematic sampling. Based on the sample set, the above linear relationship was validated for evaluating the chemical exergy of multi-component plastic wastes. The developed model had a good ability on predicting the chemical exergy of multi- component plastic wastes with a low error of less than 5%. This model required only the input of high heating value, which can be directly examined for the multi-component plastic wastes with unknown components. This study could provide a simple and effective tool for the evaluation of chemical exergy of multi-component plastic wastes. Highlights: The values of chemical exergy for six typical plastic wastes were evaluated. A linear relationship between heating value and chemical exergy of plastic waste was identified. Linear relationship could calculate accurately the chemical exergy of plastic waste mixture. An algorithm of systematic sampling for multi-component plastic wastes was developed.